Summary of N, P, and K Research with Eggplant in Florida - George Hochmuth; Ed Hanlon (EDIS, 2010)
Revised! SL330, a 13-page illustrated fact sheet by George Hochmuth and Ed Hanlon, summarizes the historical Florida research literature on nitrogen, phosphorus, and potassium fertilization of eggplant. Includes references. Published by the UF Department of Soil and Water Science, August 2010.